Assessing the Skills and Competencies Required for Computer Numerical Control Woodworking Machines for Furniture Crafts in Kano State Nigeria - Musa Nasiru Zarewa; Kareem Wahab Bamidele; Bala Maik Mohammed; Abdul Bello Kagara (CV. Media Inti Teknologi, 2025)
The study focused on assessing the skills and competencies required for Computer Numerical Control Woodworking Machines (CNCWMs) operations for furniture crafts in Kano State Nigeria. The study was conducted in some selected Government Technical Colleges (GTCs) in Kano State. Three objectives of the study were stated to guide the study. The population for the study was 158 furniture crafts teachers and students in the area of the study. There is a purposive sampling of teachers and students in the selected technical colleges’ (TCs) furniture crafts departments due to the manageable population in the department in the area of study. The instrument for data collection was a questionnaire developed from the literature reviewed and validated by three woodwork experts from the Department of Industrial and Technology Education, Federal University of Technology, Minna, Niger State – Nigeria. The questionnaire was administered to 158 respondents which included teachers and students of the furniture crafts department in three selected TCs in Kano State, and 135 were retrieved and analyzed using mean and standard deviation (SD). The study revealed among others that the skills and competencies required for CNCWMs operations for furniture crafts should be properly put into use to enhance the effective and practicable teaching of furniture crafts to improve students’ interest, understanding and comprehension in the subject, TCs to provide necessary tools and equipment that will promote the teaching and learning of furniture crafts in TCs across the country among others. Recommendations were given based on the findings from the study.